2006
DOI: 10.1189/jlb.0106013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced early vascular permeability in gelatinase B (MMP-9)-deficient mice: putative contribution of COX-1-derived PGE2 of macrophage origin

Abstract: Increased vascular permeability leading to vascular leakage is a central feature of all inflammatory reactions and is critical for the formation of an inflammatory exudate. The leakage occurs because of gap formation between endothelial cells and breakdown of the basement membrane barriers. The present study aimed to investigate the role of gelatinase B [matrix metalloproteinase 9 (MMP-9)], known to be involved in neutrophil exudation, in changes of vascular permeability at the early stages of acute zymosan pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 35 publications
4
50
1
Order By: Relevance
“…Vascular injury during mechanical ventilation is another mechanism of VILI, so the role of MMP-9 in the maintenance of the vascular wall should be taken into account. Moreover, it has been reported that these knockout mice have an increased vascular permeability after inflammation, which is mediated by prostaglandins (26). However, lack of differences in lung edema (wet-to-dry weight, protein concentration in BAL) between genotypes suggest that the protective effects are more related to the modulation of the inflammatory response than to a direct effect on vascular permeability.…”
Section: Discussionmentioning
confidence: 69%
“…Vascular injury during mechanical ventilation is another mechanism of VILI, so the role of MMP-9 in the maintenance of the vascular wall should be taken into account. Moreover, it has been reported that these knockout mice have an increased vascular permeability after inflammation, which is mediated by prostaglandins (26). However, lack of differences in lung edema (wet-to-dry weight, protein concentration in BAL) between genotypes suggest that the protective effects are more related to the modulation of the inflammatory response than to a direct effect on vascular permeability.…”
Section: Discussionmentioning
confidence: 69%
“…Since then many aspects of this inflammation have been described in detail elsewhere [2][3][4][5][6][7][8][9][10][11][12] confirming the utility of this model. Moreover, murine zymosan peritonitis models the peritoneal inflammation that often accompanies peritoneal dialyses and ulcer perforations, and its value (as such a model) is further enhanced by the (still) high morbidity rates in human peritonitis [13].…”
Section: Introductionmentioning
confidence: 85%
“…Thirty minutes later the animals were killed and their peritoneal cavities were lavaged with 1.5 ml of saline as described above. The lavage fluid was centrifuged and the absorbance of dye in the supernatant was measured at 620 nm with a Microplate Reader Expert Plus (ASYS Hitech) as described previously [5,8].…”
Section: Vascular Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, COX-1 was found to promote PGE 2 production and control the thermoregulatory response to influenza A virus infection at 4 dpi in mice (38). Mice deficient in gelatinase B (matrix metallopeptidase 9 [MMP-9]) develop a compensatory mechanism involving the COX-1-PGE 2 pathway in macrophages, resulting in enhanced early vascular permeability (39). Mounting evidence has shown that the pattern of expression of the two COX isoforms is far more complex than the general concept of constitutive (COX-1) and inducible (COX-2) expression (37,40).…”
Section: Discussionmentioning
confidence: 99%